Transformasi Digital di Dunia Pendidikan: Mengelola Sekolah Lebih Cerdas dengan Aplikasi Manajemen - Nefis Faiqotul Istiqomah; Mohammad Syahidul Haq; Karwanto; Amrozi Khamidi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
Today, people are increasingly going digital. Even though the technology of now our day is rapidly growing at speed of light, but schools have not kept pace with these developments. In fact, the school management information system has transitioned school administration and management from paper-based into a digital platform. The present study aims to highlight the significance of digital transformation in schools to overcome academic and managerial problems. Additionally, it will examine several digital management systems that are practiced along with their challenges. For this reason, the literature study method was employed to display various models of management information systems at different educational levels in Indonesia. The results of the analysis reveal that the use of management information systems provides many benefits. There are numbers of factors to consider when selecting the management information system in schools, reflecting a range of system models in operation. Each implemented system leaves specific challenges that require prompt evaluation in order maximize advantages and reduce difficulties. Based on this analysis, it can be deduced that digital advancement offers opportunities for major improvements in the efficiency, effectiveness, and quality of education that can help the decision-making process faster and more accurately. Therefore, it is important to establish proper policies and infrastructure, as well as to ensure that staff, teachers, and students are digitally literate, in order to strengthen educational performance and equip the next generation to face the challenges of the rapidly evolving digital landscape.